Antioxidant activity and phenolic composition of wine spirit resulting from an alternative ageing technology using micro-oxygenation: a preliminary study - Nocera, Anna (2020)
Aim: Alternative technologies for the aging of wine spirit, as for other spirit beverages, have been developed over the past decade in order to meet consumer and industry expectations of differentiation and sustainability. Physicochemical characterisation of the resulting products has been carried out, but no previous research has evaluated their antioxidant activity. This preliminary study examined the effect of an alternative ageing technology (micro-oxygenation combined with wood staves from chestnut or Limousin oak in 1000 L stainless steel tanks) in comparison with traditional technology (250 L new barrels) on the antioxidant activity and related phenolic composition of the wine spirit. Methods and results: The wine spirits resulting from both technologies were sampled after 8, 15, 30, 180 and 365 days of ageing. Samples taken were analysed using the DPPH method, HPLC and total phenolic index. Significantly higher antioxidant activity (50.43 % vs 36.42 % DPPH inhibition), together with greater enrichment in wood-derived compounds (51.79 vs 27.72 total phenolic index), was achieved in wine spirits aged using the alternative technology than in new barrels. Moreover, chestnut wood stood out from Limousin oak wood with higher promoted antioxidant activity (62.69 % vs 21.35 % DPPH inhibition), and higher phenolic index (49.03 vs 25.67). Significant correlations between the wine spirits’ antioxidant activity, total phenolic index, ellagic acid, gallic acid, vanillin and syringaldehyde concentrations were observed, particularly in those aged using the alternative technology. Conclusion: Micro-oxygenation combined with staves resulted in higher accumulation of bioactive compounds and antioxidant activity, thus increasing wine spirit quality and adding value to the product. Significance of the study: These preliminary results show that the characteristics acquired by the wine spirit, coupled with those revealed by previous research and the promotion of faster and cheaper ageing, make the alternative technology a promising option for the industry